Tantangan dan Peluang dalam Menerapkan Pendidikan Karakter Melalui Pembelajaran IPS di Sekolah Dasar - Erni Erni; Muhammad Kaulan Karima; Puspita Lingga; Monika Ardhana Parasmitha; Naysila Sekar Ramadhani; Ulfa Areska; Sabrina Azzahra; Ratu Ayu Aprilia Melga; Annisa Septiana Putri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This research aims to explore the challenges and opportunities in implementing character education through Social Sciences (IPS) learning in elementary schools, especially at MIN 1 Metro. Using a descriptive qualitative approach, data was collected through interviews, observation and literature study. The research results show that the main challenge lies in the diversity of student backgrounds and differences in character based on gender, which requires a different and more personalized teaching approach. On the other hand, the Independent Curriculum provides great opportunities with flexibility in planning and implementing learning that is integrated with character values. Strategies such as value reflection, collaboration between students, and strengthening teacher-student relationships have proven effective in instilling values ​​such as honesty, responsibility, tolerance, and cooperation. This research concludes that character education can be implemented optimally if it is supported by an adaptive curriculum, appropriate teaching strategies, and active involvement of teachers and parents.